Does Heart or Head Rule Donor Behaviors in Charitable Crowdfunding Markets?. Issue 4 (1st October 2016) - Gleasure, Rob; Feller, Joseph
ABSTRACT: Crowdfunding has matured into a meaningful online marketplace, both for traditional e-commerce activities and for charitable fundraising. For charities, crowdfunding presents novel donation behaviors, including those where donors may proactively seek out causes and give (often anonymously) to help others with whom they share little social connectivity. Understanding these behaviors is challenging compared to traditional fundraising behaviors, where charitable giving is partly explained by factors such as guilt avoidance, reciprocity, image, vicarious enjoyment, and group-level benefits. This suggests that some subset of charitable motivations is brought uniquely into focus in crowdfunding marketplaces. These marketplaces are often inhabited by fundseeking individuals and larger formal organizations. This adds further complexity, given that donors traditionally perceive and interact differently with charitable organizations and less formal fundraising entities. This study explores donation behavior in charitable crowdfunding based on the distinction between "pure altruism" and "warm glow" motivations. We offer a discriminatory model of donation behaviors toward individuals and organizations, which is then tested in a large-scale field study of Razoo.com. Findings suggest that donations to organizations are more influenced by outcome-related factors, such as fundraising targets and the likelihood of meeting that target, while donations to individuals are more influenced by interaction-related factors, such as the level of dialogue around a campaign.